Structure of the Ribonucleoprotein of Influenza Virus - Compans, Richard W. (1972)
The ribonucleoprotein (RNP) internal components of influenza virus were separated into distinct size classes by sedimentation in glycerol gradients and examined by electron microscopy by using positive staining with uranyl acetate. The large RNP have a peak in length distribution at 90 to 110 nm, the medium, at 60 to 90 nm, and the small, at 30 to 50 nm. These lengths can be correlated with the estimated molecular weights of the ribonucleic acids contained in the various RNP size classes. The RNP structure appears to consist of a strand which is folded back on itself and coiled in a regular double-helical arrangement.